Efficient Oxidative Degradation of Azo Dyes by a Water‐Soluble Manganese Porphyrin Catalyst. Issue 3 (7th January 2013) - Saha, Tapan Kumar; Frauendorf, Holm; John, Michael; Dechert, Sebastian; Meyer, Franc
Abstract Dyes in wastewater severely affect the nature and quality of water by inhibiting the sunlight penetration into the stream, which thereby reduces the photosynthesis reaction. This poses a serious environmental threat in many developing countries. Recently, new methods for the treatment of colored dye effluent streams have attracted much attention. The [MnIII(tmpyp)]/H2O2 system (tmpyp=meso‐tetrakis(1‐methylpyridinium‐4‐yl)porphyrinato) was now found to degrade various azo dyes with remarkably high efficiency under ambient conditions in aqueous solution at certain pH values. Main products of the catalytic degradation of the dye amaranth by [MnIII(tmpyp)]/H2O2 were analyzed. The reaction mechanism was studied in more detail by using rapid‐scan stopped‐flow spectrophotometry as a function of pH, [catalyst], [H2O2], [dye], and [surfactants]. Spectral analyses and kinetic data suggested rapid formation of an intermediate [MnIII(tmpyp)(OOH)] (a compound 0‐type intermediate), followed by the formation of a relatively stable trans‐dioxomanganese(V) porphyrin complex, [MnV(O)2(tmpyp)] (a compound I analog). The one‐electron reduction of [MnV(O)2(tmpyp)] to [MnIV(O)(tmpyp)] (a compound II analog) was accelerated greatly by amaranth. On the basis of the kinetic and spectroscopic data, a reaction mechanism of the formation of reactive intermediates [MnIII(tmpyp)(OOH)], [MnV(O)2(tmpyp)], and [MnIV(O)(tmpyp)] was proposed.